Soderžanie nekotorych vitaminov v racione pitanija i syvorotke krovi vysokokvalificirovannych sportsmenov - Radzhabkadiev, R. M.; Vrzhesinskaya, O. A.; Beketova, N. A.; Kosheleva, O. V.; Vybornaya, K. V.; Kodentsova, V. M. (Voprosy pitaniia, 2018)
The aim of the work was a comparative assessment of the vitamin status of athletes specializing in different kinds of sport (bobsleigh, dispersing and pilots, biathlon, bullet shooting) by means of assessment of the content of vitamins in the diet and blood serum. 159 professional athletes of both sexes were examined in the pre-competition period of the sport activity. The average age of the surveyed 92 men was 21.7±0.8 years, 67 women - 23.1±1.5 years. The actual data on the intake of some vitamins with the main and supplementary diet and blood serum have been presented. The basic diet of athletes didn't provide adequate intake of vitamins. The most pronounced deficiency of B vitamins and vitamin C in the basic diet was noted in female athletes specializing in bobsleigh. Only enrichment of the basic diet with specialized products for athletes and dietary supplements allowed sportsmen to increase their vitamin intake to the recommended level. At the same time, the intake of vitamins B1 and B2 with supplements in a number of athletes exceeded the upper permissible level of their consumption as a part of dietary supplements and specialized food products. The concentration of vitamins C and A in the blood serum exceeded the lower limit of the physiological norm in all athletes. At the same time, in 15.6 and 35.9% of the people, the concentration of these vitamins exceeded the upper limit of the norm. In 17.4% of the examined, a lack of vitamin E was identified, while an increased tocopherol concentration was found in 22.3% of athletes. Comparison of data on the vitamin consumption and their blood level made it possible to conclude that, in order to maintain the optimal vitamin status of the athlete's organism, it was inappropriate to use excessive doses of vitamins C (>200-300 mg/day), E (>50 mg TE/day) and A (>1500 µg RE/day). The unreasonableness of using in the diet of athletes excessively high doses of antioxidant vitamins, the increased demand for B vitamins and the appropriateness of correlating the need for B vitamins with the energy value of the diet have been discussed.